Review of the genus Novius Mulsant (Coleoptera: Coccinellidae) from China with description of four new species - Tao, Xun-Hong; Lü, Lan-Lan; Lin, Li; Zhou, Jin-Hong; Wei, Xue-Yuan; Wang, Xing-Min (Zootaxa, 2024)
N/A